MSME Strategies in Facing the Global Trade Tariff War - Sukmana, Dedy (Dinasti International Journal of Digital Business Management, 2025)
The global trade tariff war triggered by protectionist policies between countries has had a significant impact on the sustainability of micro, small, and medium enterprises (MSMEs). As a sector that contributes significantly to the Indonesian economy, MSMEs face challenges in the form of rising production costs due to import tariffs on raw materials, decreased competitiveness of export products, and global market uncertainty. This study uses qualitative methods with a literature review to analyze the impact of the global trade tariff war on MSMEs and formulate adaptive strategies that can be taken. The analysis results show that the main strategies that MSMEs can implement include market diversification, domestic market optimization, digitalization and utilization of e-commerce, product innovation based on local wisdom, increased production efficiency, and collaboration with the government and the private sector. By implementing these strategies, MSMEs are expected to be able to survive, be competitive, and continue to contribute as a main pillar of the national economy amidst global trade uncertainty